Design and development of an air tight attachment - Tan, Sandy Si Ning (2015)
Experiment was carried out to determine which hybrid material has the highest sound reduction. Specimens were saw and slotted on to the test rig that demonstrates as ear. The test rig was built to insulate sound from all directions except on the face where the specimen was slotted. Thicknesses of specimens are limited to not more than 6mm to make construction to external ear possible in the future. Two microphones were used, one for the measurement of environmental sound and the other as the ear drum (Receiving) measurements. Sound source of different output (1 kHz – 20 kHz and 30 dB to 80 dB) was generated across the specimens and transmission loss (dB) was calculated based on the data collected from the software and two models was tabulated to compare the sound reduction in between the specimens. It was shown that Heavy Duty Vinyl has the best sound reduction results not just comparing to the other two specimens but also of 5 dB to 15 dB more, depending on sound source, than a full silicone ear plug. Several factors that made Heavy Duty Vinyl having the best results in sound reduction were it has highest density and thickness as compared to the other specimens. Heavy Duty vinyl also has a rougher surface as compared to Noiseless Steel.